2014
DOI: 10.1111/ijfs.12571
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed UV light as a postprocessing intervention for decontamination of hard‐cooked peeled eggs

Abstract: Summary The efficiency of pulsed UV light (PL) for inactivation of E. coli K12 on hard‐cooked eggs was investigated. Temperature, colour and texture were recorded to determine adverse effects on quality. Distance from the quartz window (5.5, 9.5 cm) and time (1–30 s) was set as the experimental variables. Results indicated that E. coli K12 viability decreased at closer distances and increased time (P < 0.05). Bacterial populations were reduced to 3.54 log CFU per egg and 3.23 log CFU per egg after 15 and 20 s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The efficiency to inactivate E. coli on hard cooked eggs was assessed by Macias‐Rodriguez et al . (). They obtained reductions by 3·23–3·54 log without negatively affecting colour and texture, while Lasagabaster et al .…”
Section: Pl Treatment Of Other Foodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The efficiency to inactivate E. coli on hard cooked eggs was assessed by Macias‐Rodriguez et al . (). They obtained reductions by 3·23–3·54 log without negatively affecting colour and texture, while Lasagabaster et al .…”
Section: Pl Treatment Of Other Foodsmentioning
confidence: 97%
“…log may be obtained, however, at energy doses higher than 1Á75 J cm À2 , an off flavour was detected. The efficiency to inactivate E. coli on hard cooked eggs was assessed by Macias-Rodriguez et al (2014). They obtained reductions by 3Á23-3Á54 log without negatively affecting colour and texture, while Lasagabaster et al (2011) investigated the efficiency of PL to reduce Salmonella on eggshells and found reductions up to 5 log without any significant adverse effect on sensory and rheological properties of treated eggs.…”
Section: Pl Treatment Of Other Foodsmentioning
confidence: 99%
“…Enteritidis outbreaks reported from 1973 to 2009 in the United States were most frequently attributed to egg‐containing foods (Wright et al, ). Likewise, Escherichia coli O157:H7 is also a pathogenic microorganism of major public health and economic concerns (Macias‐Rodriguez, Yang, Schneider, & Rock, ). E. coli O157:H7 has been found as the cause of diarrhea and abdominal cramps with the consumption of nonpasteurized liquid egg white products (Ngadi, Smith, & Cayouette, ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a maximum log reduction of 5.3 CFU/cm 2 was obtained without any visual damage to the egg shell and its content. Macias‐Rodriguez et al () investigated the efficiency of pulsed UV light for inactivation of E. coli K12 on hard‐cooked eggs. The reduction of 3.54 log CFU per egg and 3.23 log CFU per egg were obtained after 15 and 20 s at 5.5 and 9.5 cm distance, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation